To your eternity. 8 - Oima, Yoshitoki (Kodansha Comics, 2018)
While traveling with the Guardians, Fushi is captured by Prince Bon, a man who can see the dead. Soon after, Fushi and Prince Bon embark on a journey to provide aid to the people of the land, as well as protection from Nokkers. But before long, they are faced with a force that considers Fushi's very existence to be heresy.